Penerapan Strategi Pemasaran Pada Produk UKM Keripik Pare di Kecamatan Pasekan Kabupaten Indramayu - Yudianto, Agus; Nurpratama, Meddy; Firdaus, Taufansyah (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
The need for healthy food is increasing along with population growth and increasingly limited agricultural land. However, many snack foods on the market contain additional ingredients that can be harmful to health. Therefore, healthy and nutritious snack products are increasingly needed. One interesting alternative is bitter melon chips, which are a snack product made from bitter melon, a plant that has high nutritional value. In an effort to publicize and market bitter melon chips, a business called Keripik Pare was founded by a group in West Java. The business proposal includes business ideas, capital, production planning, and marketing strategies to increase product competitiveness and business profitability and uses structured and effective implementation methods to produce quality products. By implementing SWOT analysis and the canvas business model, it is hoped that you will be able to identify business strengths, weaknesses, opportunities and threats, and design the right business strategy. In addition, the marketing strategy used includes market segmentation, determining market targets, and appropriate product placement. Through this effort, it is hoped that it can increase public awareness of the importance of consuming healthy food, create new jobs, and increase the income of local farmers.